The Young, the Old and the Innovative: The Impact of R&D on Firm Performance in ICT versus Other Sectors - Pantelis Koutroumpis; Aija Leiponen; Llewellyn D. W. Thomas (The Research Institute of the Finnish Economy (ETLA), 2017)
Although innovation opportunities within the ICT industry are assumed high in comparison with other industries because of their rapidly evolving technological trajectory, little empirical research systematically investigates the distribution of returns to R&D investment across industries and types of firms. Building on the technological opportunity framework, we examine the effect of R&D on firm revenues in a large panel of European firms and study its variation with the age, size, and sub-sector of firms. We confirm that R&D investments in ICT firms have a larger effect on their revenue performance when compared to non-ICT firms and that the effect is higher for small firms and for firms in Internet services and ICT component manufacturing. At the firm level, our results suggest that smaller and, surprisingly, older ICT firms are technologically opportunistic and exhibit the flexibility and adaptability to both identify and respond to technological opportunities and develop innovative products and services. We highlight some implications for R&D investment and policy.
Keywords: O31; O32; D24; 330; ICT; R&D; Firm performance; Technological opportunity; Firm age; Firm size